Phytochemicals Screening, Minerals Composition and Proximate Analysis of Garlic (Allium sativum) - Dauda, Maianguwa Abdulrsashid; Aliyu, Sulaiman Abubakar; Goje, Lazaru Joseph; Habibu, Bilyaminu; Joel, Emmanuel Askeb-nde; Umaru, Isaac John; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel (Darul Yasin Al Sys, 2024)
Garlic (Allium sativum) is a widely used medicinal plant with potential health benefits. The use of medicinal plants as remedies or medicine in prevention and treatment of several diseases was in place for many years. Garlic (Allium sativum) is among those plants because it possesses those characteristics. In this study, we investigated the phytochemical constituents, mineral composition, and proximate analysis of garlic. The qualitative phytochemicals screening of garlic ethanolic extract reveals the presence of Tannins, Alkaloid, Saponin, steroid, Glycosides, phenols and flavonoid while the quantitative shows that the extract composed of Alkaloid 10%, Saponin 5.30%, Tannin 4.10 µg/ml, Glycosides 4.40%, flavonoid 2.20%, phenols 3.14 µg/ml. The proximate analysis reveals that the garlic extract contains carbohydrate 65.84%, fiber 7.14%, fat 2.15%,ash 9.90%,moisture 7.58%, protein 7.30% The determination of some minerals composition in (mg/kg) reveals that the extract is composed of sodium(22mg/kg), potassium(531.5 mg/kg), zinc(7.1 mg/kg), copper(0.36 mg/kg), Iron(2.7 mg/kg), calcium(233 mg/kg) and magnesium(35.4 mg/kg) respectively were also detected, highlighting garlic's potential as a nutraceutical food supplement.. This research contributes valuable insights into the bioactive components of garlic, supporting its traditional use and potential health benefits. Further studies could explore its antioxidant, antimicrobial, and therapeutic properties.